Analisis Framing Pemberitaan Pengajuan Gugatan Hasil Pemilu 2024 di Media Online Jawapos.com dan Kompas.com - Fahmy Fahmy; Agus Saifuddin Amin (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The development of technology has transformed mass media, particularly online media, which plays a crucial role in various aspects of life, including politics. The 2024 Indonesian election, with issues of alleged fraud and power intervention, reflects a crisis of trust in democratic institutions. This study aims to analyze how online media, specifically JawaPos.com and Kompas.com, frame news coverage related to the lawsuit over the 2024 election results using Robert N. Entman’s framing analysis model. The research employs a qualitative method with a framing analysis approach, identifying four key elements: Define Problems, Diagnose Causes, Make Moral Judgment, and Treatment Recommendation. The findings reveal differences in framing between the two media. JawaPos.com highlights the administrative aspects of the lawsuit and the independence of the Constitutional Court, while Kompas.com focuses more on political dimensions such as power intervention, misuse of social assistance (bansos), and Gibran’s candidacy. In the Define Problems element, JawaPos.com emphasizes structured fraud, whereas Kompas.com underscores social assistance misuse and power intervention.